Identification of Children of Parents With Mental Illness: A Necessity to Provide Relevant Support - Reedtz, Charlotte; Lauritzen, Camilla; Stover, Ylva V.; Freili, Janita L.; Rognmo, Kamilla (Frontiers in Psychiatry, 2019)
Background: The main objective of this study was to identify and describe core life circumstances of children with mentally ill parents (COPMI) and their parents. Knowledge about COPMI aged 0-17 years is necessary, as assessment of the risk and protective factors in their lives provide solid background for preventive interventions. Methods: Participants (N = 422) were parents of minor children (N = 589) receiving treatment in the clinic for psychiatric illness and substance abuse at the University Hospital of Northern Norway. Data was drawn from electronic patient journals. Results: A total of 286 mothers and 136 fathers participated in the study, and 46.3% were single parents. Parents had 1-7 children (M = 2.24; SD = 1.02). Most parents had one diagnosis (n = 311, 73.7%), and mood disorders was the most frequent type of diagnosis. The largest proportion of parents had serious mental disorders (n = 185; 46.0%), and a large proportion of the sample was affected by disorders of moderate severity (n = 156; 38.8%). The mean age of the children was 8.6 years (SD = 4.97), and 432 children (74.6%) had one or more siblings. The large majority of children had access to adult resource persons other than the mentally ill parent (n = 424; 94%), but 6% of the children (n = 27) did not. About three quarters of the children (76.2%, n = 526) were living with the mentally ill parent (n = 401), and 170 children (32.5%) lived with a single parent with a mental health disorder and siblings, full time or part of the time. The odds that parents had informed their children about the treatment/hospitalisation and condition was higher the older the child was (p <. 001), and the youngest children rarely got necessary information about this. Discussion: Risk and protective factors associated with the children’s ages, access to resource persons, information about the parent’s health problems and treatment are discussed in relation to different preventive steps for COPMI.